The Pursuit of Preparing a Professional and Humane Teacher What Lies behind the National Curriculum Framework for Teacher Education 2009 - Singh, Bhupendra; Mishra, Patanjali (JOURNAL OF INDIAN EDUCATION, 2019)
Every teacher is charged to deliver the curriculum to their students. But a humane teacher makes sure to teach the curriculum in a meaningful way to one's students so that they can share its implications beyond the classroom walls. Kilpatrick envisaged the curriculum as “a series of experiences in which, by guided induction, the child makes his own formulations. Then they are his to use” (quoted in Pinar et al., 2008, p. 116). The teacher education curriculum is a plan that is related to develop a competent and humane teacher by empowering one to face the challenges before education and society. Therefore, an assured way of making a curriculum more attractive, inspiring and applicable is to implement it through humane education materials and promote the ideas of learners. This research article focuses on the aim of the National Curriculum Framework for Teacher Education (NCFTE) 2009 behind preparing a professional and humane teacher.